Do que falamos quando falamos de música experimental: experiência estética e música experimental na sociedade de consumo - Gonzalez, Fernando (2021)
The purpose of this research is to understand the configuration of the experimental music as a commodity in the context of the consumer society and its relationship as an aesthetic proposal with the media culture in which it is inserted. For that, we seek to propose a debate that encompasses specificities of the aesthetic experience, understanding the current moment as highly mediatized, spectacularized and crossed by the practices and dynamics of the culture industry. The research focuses on experimental music composers who gravitate towards contemporary music such as John Cage, Christian Wolff, Michael Nyman, Terry Riley, Steve Reich and Alvin Lucier. We begin by seeking an understanding of experimental music as a communicational phenomenon and an aesthetic proposal, based on Cage, Nyman, Gottschalk and Lucier. From the observation of pieces by these composers, some of the characteristics of the genre as an aesthetic proposal are analyzed, tensioning elements of contemporary media society, showing apparent inconsistencies with cultural consumption practices and characteristics of the culture industry. For this, ideas from Simmel, Benjamin, Türcke, Baudrillard, Debord, Canevacci and Rancière are articulated. From Gottschalk onwards, we observe how experimental music is far from the productions strongly identified with the culture industry, which we detail with Adorno and Horkheimer, Duarte and Safatle. Next, we present a genealogy of the experimental music, showing the context of its emergence with contributions from Beal, Monod, Rosen, Taruskin, Elias, Ross and Iddon, and we follow with a debate on postmodernity from Eagleton, Jameson, Anderson, Harvey, Lyotard and Rouanet. We reflect on the conflicts of capital involved in consumer relations with music and in the experience of musical circuits and dynamics of musical genres, with ideas from Bourdieu, Janotti Jr. and Janotti Jr. and Sá. We also focus on the notion of distinction, offering a proposal to update it based on a debate articulating the concept with criticisms of its implications provided by Peterson and Kern, van Eijck and Coulangeon and Yemel. We then move on to discuss the artistic vanguards in the context of an analysis of the political potential of experimental music, with Bürger, Sontag, Pareyson, Adorno and Rancière. Finally, we trace a genealogy of consumption as a social and cultural phenomenon with McCraken, Baccega, Fontenelle, Canclini, Douglas and Isherwood, Rocha, A and Silva, JG, Slater, Rocha and Silva, Rocha, and Barros Filho and Lopes. We end with the results of an observation of the consumption practices of experimental music fans, articulating it with the theoretical work woven so far. We developed this research through bibliographic analysis and media records on experimental music and aesthetic analysis of pieces by selected composers, as well as qualitative interviews and observational research of practices developed by consumers of the genre. At the end, we consider experimental music a media product with an aesthetic proposal strongly dissonant from that most frequently observed in massive popular music, presenting political potential which, by mobilizing issues other than those of the musical mainstream, opens space for emancipatory practices endowed with negativity and aesthetic potency.